EARTHQUAKE DISASTER EDUCATION IMPROVES PREPAREDNESS FOR STUDENTS AT ELEMENTARY SCHOOL OF JIGUDAN SRANDAKAN BANTUL INDONESIA - niken setyaningrum; Pipin Nurhayati (Journal of Health Community Service, 2021)
Bantul district is an earthquake-prone area because it is close to the south coast area, it is traversed by plates that cause disasters. One of the disaster mitigation efforts is to prevent the number of victims when an earthquake occurs. It is necessary to increase understanding and change people's behavior. One of the right targets is elementary school students because education at an early age will affect behavior. Earthquake disaster education is a disaster mitigation effort. The indicator is the measurement of the level of earthquake preparedness using a questionnaire. Education is carried out for students in grades 3, 4, and 5 of the Elementary School of Jigudan Srandakan Bantul. The school is located in the red zone. The results of these measurements are mostly in the ready category with a score of 65 – 79 as many as 42 students. It is important to continue the education to improve earthquake disaster mitigation.